2015
DOI: 10.1080/17458080.2015.1100333
|View full text |Cite
|
Sign up to set email alerts
|

Unmodified gold nanoparticles as a colorimetric probe for visual methamphetamine detection

Abstract: In recent years, in addition to the classic drugs, addiction to a series of new drug classes known as club drugs has increased significantly. Fast and lowcost bioassay for the detection of amphetamine-based drugs can be an effective strategy towards reducing their abuse. In this study, we designed a sensitive bioassay strategy using gold nanoparticles (GNPs) and the aptamers that possess high affinity toward methamphetamine (MA). It is suggested that the aptamer adopts different tertiary structures in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…These systems can be formed in two formats which are solution-based and flat substrate-based assays. The literature survey of the detection of abused drugs is abundant of optical biosensors, using colorimetric [119][120][121][122][123][124][125][126][127], fluorescence-based [86,[128][129][130][131][132], chemiluminescence-based [133][134][135], and SPR-based techniques [136]. The results from the literature survey are summarized in Table S2.…”
Section: Optical Aptasensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…These systems can be formed in two formats which are solution-based and flat substrate-based assays. The literature survey of the detection of abused drugs is abundant of optical biosensors, using colorimetric [119][120][121][122][123][124][125][126][127], fluorescence-based [86,[128][129][130][131][132], chemiluminescence-based [133][134][135], and SPR-based techniques [136]. The results from the literature survey are summarized in Table S2.…”
Section: Optical Aptasensorsmentioning
confidence: 99%
“…However, the literature on colorimetric aptasensors for abused drugs is not very fruitful, to the best of our knowledge, only eight studies were conducted in this field. AuNPs [119,120,123,125,127,149,150], Au@Ag core-shell nanoparticles [124], and 4, 4'-diamino-3, 3', 5, 5'-tetramethylbiphenyl (TMB) [121,122,126] chemistry were used as the colorimetric agents. Mostly, simple Eppendorf or µ-well-based techniques were established and used for the detection of cocaine and methamphetamine [121][122][123][125][126][127]149,150].…”
Section: Colorimetric Aptasensors For Abused Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that aptamers undergo ligand-induced conformational changes that can be sensed by Au NPs. This method can be used as a simple and promising colorimetric probe for aptamer-based sensors (Xia et al 2010); in fact, the colour change of Au NPs through addition of salt can be used to detect the presence or absence of analytes that cause conformational changes in aptamers (Yarbakht & Nikkhah 2016). Many other target analytes have already been detected using this strategy such as enzymes, proteins, ions and other small molecules (Chen et al 2010a;Chandrawati & Stevens 2014;Cheng et al 2015).…”
Section: 6mentioning
confidence: 99%